ENHANCING THE EFFICIENCY OF METALLIC ORE EXPLORATION THROUGH THE INTEGRATION OF GEOLOGICAL, GEOPHYSICAL, GEOCHEMICAL, AND GIS DATA IN THE NORTHERN AND CENTRAL PARTS OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
This study explores approaches to improving the efficiency of exploration for gold, polymetallic, and porphyry copper deposits within the Lori, Stepanavan, and Pambak-Tsaghkunyats ore districts of the Republic of Armenia. An integrated analysis of the geological framework, gravity, aeromagnetic, and geochemical survey data, combined with GIS-based techniques, was used to identify the principal ore-controlling factors governing the distribution of endogenous mineralization. The locations of several fault structures were refined, previously unrecognized concealed circular and arcuate structures were delineated, and their relationships with known mineral occurrences were established. The spatial association of gold, polymetallic, and porphyry copper mineralization with specific gravity anomalies, major fault zones, and intrusive complexes of different compositions was demonstrated. Several prospective target areas for detailed exploration were identified, and a preliminary assessment of their mineral potential was conducted. The results obtained may be applied to mineralization forecasting, and the planning of future geological exploration programs.
Keywords: gold; polymetallic mineralization; porphyry copper deposits; ore-controlling structures; GIS analysis; geochemical and geophysical characteristics; mineral exploration